Levas Vladimirovas Conception of Bibliophilia - Liepaitė, Inga (Bibliotheca Lituana, 2014)
Professor Levas Vladimirovas may be considered as one of the most outstanding and productive representatives of librarianship, book science and information sciences of the second half of the 20th century in Lithuania. On the basis of published and unpublished sources this article attempts for the first time to review the professor’s activities and role in the organized movement of book lovers which started in 1974 and which has not been disclosed and evaluated until now. The research reveals the situation of Lithuanian bibliophilia in the interaction of possibilities and restrictions of the Soviet period, the conditions under which it could exist, and the interpretation of its conception on the ideological level. The coverage of a broader context allowed to assess L. Vladimirovas’ attitude towards bibliophilia and its functions impartially. Although professor’s heritage, related to issues of bibliophilia history and theory, is not large, nevertheless his insights enable to conceive the general conception of bibliophilia in Soviet Lithuania that has been formed on the ideological level better and significantly supplements it. It must be noted that L. Vladimirovas has not avoided the tendency of dual understanding of bibliophilia characteristic to the Soviet period. He treated bibliophilia either as an elementary liking of books, accumulating books or simply love for books, or as collecting of rare and valuable books to which he traditionally looked unfavourably and identified it with snobbish bibliophilia or bibliomania. In his works and his outgivings both in the Soviet period and in the period of independent Lithuania L. Vladimirovas described bibliophilia as a mass phenomenon.
Keywords: none